Empowerment of fishermen in managing processed Rebon Shrimp-Based Food Products in Coastal "Communities" - Isir, Mariana; Abdullah, Vera Iriani (OMNICODE Journal (Omnicompetence Community Developement Journal), 2021)
The fishing community is one of the communities identified as poor, about 90% of the 16.2 million people are below the poverty line, the abundant marine wealth should be able to support the economy, but in reality it is not as expected. Poverty experienced by the community has an impact on the health status of the family including the inability to access health facilities, Chronic Energy Deficiency in pregnant women and malnutrition in children. Rebon shrimp is a marine product that contains multi micronutrients, has direct benefits for health and can be processed into various products. Raw rebon shrimp in the market are sold at very cheap prices ranging from Rp. 60,000- s/d 90,000/ Kilo, the fragrant and distinctive smell has its own charm, but the low knowledge of mothers in producing household processed food products, product packaging, business licensing, and marketing of products is a common obstacle to product development. nutritious and hygienic. For this reason, through this Community Service activity, training on Food Product Processing made from rebon shrimp will be carried out which can help increase family income. The main target partners include women fishermen, head of RT, head of RW, TP-PKK, Posyandu cadres, while supporting partners are the head of the West Sorong District, Department of Health, Health Polytechnic of Sorong and the Department of Industry. The implementation time is 2 days, starting on June 10, 2021 until June 11, 2021. Mandatory output results in the form of scientific publications in accredited national journals. While the additional output in the form of intellectual property rights.